Intravital Dynamic and Correlative Imaging of Mouse Livers Reveals Diffusion‐Dominated Canalicular and Flow‐Augmented Ductular Bile Flux. Issue 4 (16th March 2021) - Vartak, Nachiket; Guenther, Georgia; Joly, Florian; Damle‐Vartak, Amruta; Wibbelt, Gudrun; Fickel, Jörns; Jörs, Simone; Begher‐Tibbe, Brigitte; Friebel, Adrian; Wansing, Kasimir; Ghallab, Ahmed; Rosselin, Marie; et al.
Abstract : Background and Aims: Small‐molecule flux in tissue microdomains is essential for organ function, but knowledge of this process is scant due to the lack of suitable methods. We developed two independent techniques that allow the quantification of advection (flow) and diffusion in individual bile canaliculi and in interlobular bile ducts of intact livers in living mice, namely fluorescence loss after photoactivation and intravital arbitrary region image correlation spectroscopy. Approach and Results: The results challenge the prevailing "mechano‐osmotic" theory of canalicular bile flow. After active transport across hepatocyte membranes, bile acids are transported in the canaliculi primarily by diffusion. Only in the interlobular ducts is diffusion augmented by regulatable advection. Photoactivation of fluorescein bis‐(5‐carboxymethoxy‐2‐nitrobenzyl)‐ether in entire lobules demonstrated the establishment of diffusive gradients in the bile canalicular network and the sink function of interlobular ducts. In contrast to the bile canalicular network, vectorial transport was detected and quantified in the mesh of interlobular bile ducts. Conclusions: The liver consists of a diffusion‐dominated canalicular domain, where hepatocytes secrete small molecules and generate a concentration gradient and a flow‐augmented ductular domain, where regulated water influx creates unidirectional advection that augments the diffusive flux.